Colectomy Rates did not Decrease in Paediatric- and Adult-Onset Ulcerative Colitis During the Biologics Era: A Nationwide Study From the epi-IIRN. (20th November 2021) - Atia, Ohad; Orlanski-Meyer, Esther; Lujan, Rona; Ledderman, Natan; Greenfeld, Shira; Kariv, Revital; Daher, Saleh; Yanai, Henit; Loewenberg Weisband, Yiska; Gabay, Hagit; Matz, Eran; Nevo, Daniel; et al.
Abstract: Background: It is still of debate whether the advent of biologics has been associated with a change in the natural history of ulcerative colitis [UC]. In this nationwide study we evaluated trends of long-term outcomes in all patients diagnosed with UC in Israel during the biologic era. Methods: Data in the epi-IIRN cohort were retrieved from the four Israeli Health Maintenance Organizations covering 98% of the population, and linked to the Ministry of Health prospective registry on surgeries and hospitalizations. Joinpoint Regression and Kaplan–Meier survival analyses were used, reporting annual average percentage change [AAPC] for each outcome. Results: A total of 13 231 patients were diagnosed with UC since 2005 (1426 [11%] paediatric-onset, 10 310 [78%] adults, 1495 [11%] elderly) with 93 675 person-years of follow-up. The probabilities of surgery after 1, 3 and 5 years from diagnosis were 1.1, 2.3 and 4.1%, respectively, and the corresponding rates of hospitalizations were 22, 33 and 41%. The overall utilization of biologics in UC increased from 0.1% in 2005 to 9.6% in 2019 [AAPC 22.1%] and they were prescribed earlier during the disease course (median of 5.6 years [interquartile range 2.8–9.1] in 2005–2008 vs 0.8 years [0.4–1.5] in 2015–2018; p < 0.001]. Annual rates of surgeries [AAPC −1.3; p = 0.6] and steroid-dependency [AAPC −1.2; p = 0.3] remained unchanged, while rates of hospitalizations slightly decreased [AAPC −1.2; p < 0.001]. Outcomes were consistently worse in paediatric-onset disease than in adults, despite higher utilization of biologics [28% vs 12%, respectively; p < 0.001]. Conclusion: During the biologic era rates of surgeries and steroid-dependency have remained unchanged in patients with UC, while rates of hospitalizations have slightly decreased.